Cardiac extracellular matrix modulation in a rat-diabetic model: biochemical and anti-oxidant beneficial effect of pomegranate (Punica granatum) peel extract. (2nd January 2022) - Dab, Houcine; Chehidi, Amel; Tlili, Mounira; Ben Saad, Anwar; Khabir, Abdelmajid; Zourgui, Lazhar
Abstract: Context: Disorders associated with diabetes and the beneficial effects of pomegranate peel extract (PPE) were widely reported. However effect of diabetes and PPE on extracellular matrix (ECM) remodelling needs further investigation. Objectives: The focus of this study was to investigate the involvement of diabetes in cardiac ECM and the beneficial effects of PPE. Methods: Diabetes was induced by alloxan. PPE group was injected with 100 mg/kg of PPE. The phenolic profile of PPE was analyzed by HPLC. ECM was detected by ELISA. MMP-1, -8, -13 were determined by a colorimetric assay. Results: Compared to control fibronectin and laminin plasma content was higher respectively by 69% and 42% ( p  < 0.05) in diabetes. LV content of hydroxyproline and total collagen was higher by 195% ( p  < 0.01) and 56% ( p  < 0.05) in the diabetic group compared to control and restored at a similar level to controls in the PPE group. Compared to control, collagenase activity was significantly reduced by 32% ( p  < 0.05) and 35% ( p  < 0.05) respectively in ALX and PPF groups. There is no significant difference in collagenase activities in diabetic rats after and before PPE injection. Conclusion: Diabetes is involved in cardiac ECM remodelling which can be improved by PPE. These findings will be useful for more understanding diabetes-induced cardiac disorders.